ACE inhibitor-induced intestinal angio-oedema: rare adverse effect of a common drug. (22nd July 2013) - Shahani, Lokesh
Abstract : ACE inhibitors are the leading cause of drug-induced angio-oedema in the USA. ACE inhibitor-induced intestinal angio-oedema, a much rarer complication of this medication, has been reported. The author reports a patient presenting with a 1-day history of severe abdominal pain. The patient was started on lisinopril 2 days prior to this presentation. Computer axial tomography (CAT) scan of the abdomen demonstrated extensive and marked thickening, and oedema involving the duodenum and proximal jejunum associated with significant mesenteric oedema. Concerns for visceral angio-oedema and a possible association with lisinopril according to the Naranjo algorithm were raised. Lisinopril was discontinued and the patient was treated with antihistamines. The patient improved clinically in the next 24 h and discharged home with education and documentation of this serious allergy. ACE inhibitor-induced visceral angio-oedema is under-reported and most often missed resulting in waste of hospital resources towards working up this clinical diagnosis.